Comparative resource productivity of oyster (Pleurotus ostreatus p.) and button mushrooms (Agaricus bisporus j.) in Kathmandu, Nepal - Shrestha, Lal K; Dhakal, Shiva C (Journal of Agriculture and Environment, 2014)
The study was conducted to analyze the comparative economics of oyster (Pleurotus ostreatus P.) and button mushrooms (Agaricus bisporus J.) in Kathmandu district of Nepal during the year 2012 with the objective to compare their resource productivity. Primary data were collected from semi-structured pretested questionnaire from purposively selected 45 growers from each category. The examination of resource use efficiency showed that most of the resources were not used efficiently and there is further scope of commercialization. It is imperative to banks for investment in mushroom. Study revealed materials are to be decreased in case of oyster mushroom and labor use is to be increased in button mushroom. It is suggested to cultivate button mushroom instead of oyster as button mushroom has increasing return to scale. It was concluded that the mushroom farming was highly profitable and suggested to cultivate button mushroom in long run and oyster mushroom in short run.